2013
DOI: 10.1016/j.heares.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

‘Ecstasy’ enhances noise-induced hearing loss

Abstract: ‘Ecstasy’ or 3,4-methylenedioxy-N-methamphetamine (MDMA) is an amphetamine abused for its euphoric, empathogenic, hallucinatory, and stimulant effects. It is also used to treat certain psychiatric disorders. Common settings for Ecstasy use are nightclubs and “rave” parties where participants consume MDMA and dance to loud music. One concern with the club setting is that exposure to loud sounds can cause permanent sensorineural hearing loss. Another concern is that consumption of MDMA may enhance such hearing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
1
6
0
1
Order By: Relevance
“…The ABR recordings of the three experimental groups evaluated displayed a distinctive pattern characterized by four to five evoked waveforms following the stimulus onset (Figure 2 ). Consistent with previous findings (Overbeck and Church, 1992 ; Church et al, 2010 , 2012a , b , 2013 ; Alvarado et al, 2012 ), wave II was the largest of all waves, followed by waves I, IV, V, and finally by wave III, which was the smallest of the waves that comprised the ABR (Figure 2 ). However, despite the similarities among the three groups, there was an apparent decrease in the amplitude of all waves as the age of the rats increased (compare Figures 2A–C ).…”
Section: Resultssupporting
confidence: 91%
“…The ABR recordings of the three experimental groups evaluated displayed a distinctive pattern characterized by four to five evoked waveforms following the stimulus onset (Figure 2 ). Consistent with previous findings (Overbeck and Church, 1992 ; Church et al, 2010 , 2012a , b , 2013 ; Alvarado et al, 2012 ), wave II was the largest of all waves, followed by waves I, IV, V, and finally by wave III, which was the smallest of the waves that comprised the ABR (Figure 2 ). However, despite the similarities among the three groups, there was an apparent decrease in the amplitude of all waves as the age of the rats increased (compare Figures 2A–C ).…”
Section: Resultssupporting
confidence: 91%
“…34 With regard to alcohol consumption, Upile et al 16 observed a positive association between breath alcohol concentration and the magnitude of hearing thresholds when exposed to recreational noise. Apart from the previously mentioned case report, 18 the association between MDMA and NIHL was studied only in animals; a study in rats 35 showed that the combination of MDMA and noise enhances the effect of noise on NIHL. Alcohol and drug use are known to occur at music festivals.…”
Section: Discussionmentioning
confidence: 99%
“…It is also documented that Aldous Huxley, the eminent philosopher and novelist, has requested his wife to administer LSD to him while lying on his deathbed suffering from a non-treatable form of laryngeal cancer (Dyck, 2015).There is a considerable lack of data based on reliable inference concerning cases of deafness induced by psychedelics and other psychoactive chemicals. However, case reports exist in connection with ecstasy, methadone, benzodiazepines, heroin, opioids, as well as polysubstance narcotic overdose (Fisman, 1991;Sharma, 2001;Christenson et al, 2010;Schreiber et al, 2010;Sara et al, 2011;Schweitzer et al, 2011;Lopez et al, 2012;Church et al, 2013;Saifan et al, 2013;Aulet et al, 2014;Novac et al, 2015). The majority of these chemicals can induce sensor neural hearing loss which can be either unilateral or bilateral.…”
Section: Resultsmentioning
confidence: 99%